Immunological properties of Andean starch films are independent of their nanometric roughness and stiffness - Torres, F.G.; Troncoso, O.P.; Gamucci, O.; Corvaglia, S.; Brunetti, V.; Bardi, G. (Elsevier, 2015)
Starch is a natural material extracted from roots, seeds, stems and tubers of different plants. It can be processed as a thermoplastic to produce a variety promising products for biomedical applications, including foams, sheets and films. In the present work, we investigated the immunological properties of microfilms prepared with starches extracted from six different types of Andean potatoes and their relationship with the different film-surface features. We confirmed the biocompatibility of all the films using THP-1 human monocytes, noticing only slight decrease in cell viability in two of the tested starches. We also analyzed pro-inflammatory cytokine release and immune cell surface receptor modulation on THP-1 plated onto the films. Our data show differences in the immunological profile of the same cells cultured onto the different starch films. Furthermore, we examined whether the dissimilar stiffness or the nanometric roughness of the films might influence the immune stimulation of the THP-1 monocytes. Our results demonstrate no correlation between cultured THP-1 immune activation and surface film characteristics. We conclude that different Andean native potato starch films have specific ability to interact with cell membranes of immune cells, conceivably due to the different spatial localization of amylose and amylopectin in the diverse starches.
Keywords: Biocompatibility; Andean potatoes; https://purl.org/pe-repo/ocde/ford#3.02.01